Amplification and overexpression of CMET is a common event in brain metastases of non‐small cell lung cancer. Issue 5 (5th August 2014) - Preusser, Matthias; Streubel, Berthold; Berghoff, Anna S; Hainfellner, Johannes A; von Deimling, Andreas; Widhalm, Georg; Dieckmann, Karin; Wöhrer, Adelheid; Hackl, Monika; Zielinski, Christoph; Birner, Peter
Abstract : Background: CMET represents an emerging therapy target for monoclonal antibodies and tyrosine kinase inhibitors in non‐small cell lung cancer (NSCLC). Methods: We investigated C MET gene amplification status by fluorescence in‐situ hybridization (FISH) and CMET protein expression by immunohistochemistry in a large series of 209 NSCLC brain metastases (BM; 165 adenocarcinoma, 20 squamous cell carcinoma, 11 adenosquamous carcinomas, 11 large cell carcinomas and two large cell neuroendocrine carcinomas) and correlated our results to clinic‐pathological parameters and molecular data from previous studies. Results: We found CMET gene amplification in 36/167 (21.6%) and CMET protein expression in 87/196 (44.4%) of evaluable BM. There was a strong correlation between the presence of C MET gene amplification and CMET protein expression ( P  < 0.001, chi‐square test). Furthermore, presence of C MET amplification correlated positively with presence of ALK amplifications ( P  = 0.039, chi‐square test) and high HIF1 alpha index ( P  = 0.013, Mann–Whitney U ‐test). Neither CMET expression nor CMET gene amplification status correlated with patient outcome parameters or known prognostic factors. Conclusions: CMET overexpression and CMET amplification are commonly found in NSCLC BM and may represent a promising therapeutic target.